2020
DOI: 10.3390/su12187276
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Job Retention Intention of Nurses Based on Social Support in the COVID-19 Situation

Abstract: This study investigated how social support influences the job engagement and job retention intention of nurses struggling in the continuing scenes of the COVID-19 pandemic. To this end, 382 nurses were the participants, data from 377 of whom were analyzed in total, with the following results. First, it showed that nurses’ job engagement and job retention intention were high, depending on their age and work experience. Second, in terms of the factors related to COVID-19, the group with experience in nursing pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
88
2
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(103 citation statements)
references
References 35 publications
3
88
2
10
Order By: Relevance
“…The fear of personal safety and well-being of colleagues and family are all constraining factors, which distress and influence staff working attitudes during pandemics [ 31 ]. Nurses with experience in nursing patients infected with COVID-19 and nurses working in COVID-19 divisions had shown to have low job-retention intentions due to their emotional concerns and fear of becoming infected [ 32 ]. Chafee also reported that certain factors, such as the type of disaster, concern for family, pets, and personal safety have an impact on the willingness of staff to work during disasters [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…The fear of personal safety and well-being of colleagues and family are all constraining factors, which distress and influence staff working attitudes during pandemics [ 31 ]. Nurses with experience in nursing patients infected with COVID-19 and nurses working in COVID-19 divisions had shown to have low job-retention intentions due to their emotional concerns and fear of becoming infected [ 32 ]. Chafee also reported that certain factors, such as the type of disaster, concern for family, pets, and personal safety have an impact on the willingness of staff to work during disasters [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…They could also identify possible differences in job engagement and job-retention intention due to the category and type of social support. These results suggest that social support should be provided strategically to ensure nurses' job retention [11].…”
mentioning
confidence: 92%
“…It can reduce the anxiety level of people (e.g., patients) in stressful life events [29] and is positively correlated with mental and physical health [30,31]. Studies have revealed that social support can reduce depression and anxiety [32] and affect people's psychological condition and alleviate anxiety, depression, and stress, contributing to post-disaster psychological recovery [21,33]. In order to improve public mental health in the context of the COVID-19 outbreak, the Chinese government has taken the following social support measures in terms of social support: (1) information support [34]-government and relevant departments are providing real-time disclosure of COVID-19-related knowledge and updates;…”
Section: Introductionmentioning
confidence: 99%